2002
DOI: 10.1146/annurev.immunol.20.090501.112049
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanism of Class Switch Recombination: Linkage with Somatic Hypermutation

Abstract: Class switch recombination (CSR) and somatic hypermutation (SHM) have been considered to be mediated by different molecular mechanisms because both target DNAs and DNA modification products are quite distinct. However, involvement of activation-induced cytidine deaminase (AID) in both CSR and SHM has revealed that the two genetic alteration mechanisms are surprisingly similar. Accumulating data led us to propose the following scenario: AID is likely to be an RNA editing enzyme that modifies an unknown pre-mRNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
451
1
3

Year Published

2004
2004
2010
2010

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 549 publications
(457 citation statements)
references
References 258 publications
2
451
1
3
Order By: Relevance
“…Others have hypothesized that bcl-3 directly regulates class switch recombination and somatic hypermutation, because these genetic alterations closely correlate with transcriptional activation of the immunoglobulin genes. 21 BCL-3 also can bind to the promoter of cyclin D1, enhancing progression of the cell cycle from G1 to S phase. 4,22 Several studies have shown that BCL-3 is activated and may play a role in human breast cancer, 23 mouse skin carcinogenesis, 24 and hepatocyte proliferation, 25 which suggest that BCL-3 is involved in carcinogenesis and cell growth.…”
Section: Bcl-3 In Lymphomasmentioning
confidence: 99%
“…Others have hypothesized that bcl-3 directly regulates class switch recombination and somatic hypermutation, because these genetic alterations closely correlate with transcriptional activation of the immunoglobulin genes. 21 BCL-3 also can bind to the promoter of cyclin D1, enhancing progression of the cell cycle from G1 to S phase. 4,22 Several studies have shown that BCL-3 is activated and may play a role in human breast cancer, 23 mouse skin carcinogenesis, 24 and hepatocyte proliferation, 25 which suggest that BCL-3 is involved in carcinogenesis and cell growth.…”
Section: Bcl-3 In Lymphomasmentioning
confidence: 99%
“…It hypothesizes that at least some cancer-related mutations are introduced by activation-induced cytidine deaminase (AID), an enzyme that is expressed in activated B lymphocytes, and is required for somatic hypermutation (SHM) and class-switch recombination of antibody genes (Honjo et al, 2002). The hypothesis is based on the following observations: (1) AID can induce mutations in non-B cells (Yoshikawa et al, 2002); (2) AID transgenic mice develop various tumours, including T-cell lymphoma and lung microadenoma (Okazaki et al, 2003) and (3) AID can be induced in human hepatic, gastric and biliary epithelial cells when stimulated with pro-inflammatory cytokines, such as transforming growth factor-b and tumor necrosis factor-a, and when challenged with pathogens, such as hepatitis C virus (HCV) and Helicobacter pylori.…”
Section: Introductionmentioning
confidence: 99%
“…A widely accepted model is that AID initiates CSR by deamination of cytidine residues in S regions thus creating uracils and the resulting mismatches are recognized by specific enzymes and excised, leading to DNA double strand breaks (DSBs) (Nussenzweig and Alt, 2004;Rada et al, 2002). An alternative model is that AID might edit mRNAs to produce proteins essential for initiating the CSR and SHM reactions (Honjo et al, 2002;Honjo et al, 2004). In both models, recognition and repair of these DSBs are critical for successful completion of CSR (Kaminski and Stavnezer, 2004;Nussenzweig and Alt, 2004;Honjo et al, 2002;Bassing and Alt, 2004).…”
Section: Introductionmentioning
confidence: 99%